Autonomous learning features: A case study in an Indonesian ESP classroom - Budianto, Langgeng; Mason, Andrea R (Universitas Muhammadiyah Sidoarjo, 2022)
This article explores autonomous learning features and effective strategies for meeting the needs of the autonomous learner. A 4-month ethnographic study examined the learning features of three non-English major undergraduates enrolled in an English for Specific Purposes (ESP) course at an Indonesian university. The study also explored the students’ and teacher’s understanding of how the ESP classroom can benefit the autonomous learner. Data gathered through interviews, focus group discussions, and classroom observation indicate four key autonomous learning features: 1) a willingness to accept responsibility; 2) dedicated planning; 3) implementing effective strategies; and 4) monitoring progress. The findings also indicate that a variety of scaffolded and authentic learning materials combined with a flexible and creative teaching approach enhance autonomous learning. We also address how our results are applicable to most educational situations as autonomous learning is not limited to the language classroom. HIGHLIGHTS: The three subjects indicated different processes of autonomy such as monitoring learning progress using a specific task, holistic approach, and regular reflection strategies. Adopting and promoting a spirit of independent learning provides ESP learners with a supportive framework to develop and practice autonomous learning habits The ESP learners not only required to learn general English but also to learn specific English (their content knowledge in English) as their major. This is the novelty of the study. Therefore, this study provides specific add to the theory of autonomous learning.